Territoires méridionaux et îles australes : laboratoires du masculin dans les premiers romans d’aventures pour garçons victoriennes - Valentine Prévot (Cahiers Victoriens et Edouardiens)
The South is ubiquitous within the extensive corpus of the first Victorian boys’ adventure stories. These southern and austral spaces, from the Mediterranean coasts to the South Seas, welcome the young British heroes of these novels which were absolute bestsellers. My paper will interrogate how this southern space, eccentric and off-center, turns into a laboratory of the British masculine identity, drawing the outside towards the inside, the periphery towards the centre and the Other towards the Same. Through the trials and tribulations of Jack Easy in Marryat’s Mr. Midshipman Easy (1838) and the shipwreck of both the Henniker family in Marryat’s The Little Savage (1848) and the three heroes of Ballantyne’s The Coral Island (1858), the British imperial space spreads out at the same time as welcoming and heavenly but also as ferocious and unyielding. After an initial moment of clash and violence, these spaces allow themselves to be appropriated before turning into zones of contact. The encounter with cannibals, pirates or even women, generates frictions and redefinitions of the hegemonic masculine identity embodied by our young heroes. These southern spaces then materialize new conditions of possibility for the creation of a fluid, unstable and moving masculinity, key adjectives that define the Victorian culture. The repeated contacts with the space of the Other not only authorize a quest for the purification of masculinity, the conquest of territories and numerous experiences of hybridization, it also enables us to redefine the Same which eventually absorbs the Other when the British heroes inevitably go back to their island home. These southern and austral spaces, apparently marginal, end up being devoured by and swallowed in the centre, becoming the centre in their turn.